A sample of orientalist suspicious contained in the internet and the response - Yousef A. Baker, El-Ebiary; Mohammed Ebrahim, El Sherbiny Sakr (2020)
In the era of the Internet, the Sunnah of the Prophet, may God’s prayers and peace be upon him, was subjected to many and various slanders; the enemies of Islam persisted in undermining them and raising suspicions around them, sometimes by challenging their argument, sometimes by contradicting them, and sometimes by opposing the Holy Qur’an and reality.Among those who contested the problematic hadiths: the orientalists and their followers, they raised in this time the contradictions of other prophets in the past ages, which the prophets had contradicted, claiming that the Prophet commanded his companions not to write the Sunnah, which led to the loss of the Sunnah and not its codification in The first era of Islam, which prompted the modernists in the following eras to put the hadiths from themselves or convey them from the People of the Book and their attribution to the Prophet, as this led to their contradiction and opposition. Among these hadiths are the hadiths of killing dogs and their acquisition. Orientalists have claimed that there is a contradiction between these hadiths, as there are hadiths ordering the killing and non-possession of dogs; other hadiths that allow them to be acquired and not killed; and Orientalists claimed that Muslim scholars could not reconcile these hadiths.These orientalists have followers who followed their path, followed their trail, and published these suspicions, and they took from the internet sites a platform for them to transmit these toxins, and among these sites are the atheistic Arab sites that are skeptical of the Prophet’s Sunnah.Therefore, we will shed light on this suspicion and what the plagues raised about it, we follow their sayings, while responding to them and dropping their arguments, by presenting the sayings of the trustworthy scholars who served the prophetic Sunnah, denying it to distort the precious, plagiarize the deceitful, and interpret the ignorant.